(untitled) (Research, Society and Development, 2022)
The present study aimed to evaluate the effects of the menstrual cycle on the total volume of training, associated with the subjective perception of effort in each phase. The intentional non-probabilistic sample was made up of 20 eumenorrheic women, who were allocated into two groups: Group NA (which does not use a medicated contraceptive method) composed of ten women; AT group (users of pharmacological contraceptives). To achieve the proposed objectives, the research carried out training for lower limbs until momentary muscle failure in four different phases of the menstrual cycle. The results obtained indicate the influence of the menstrual cycle on the total training volume, so that in the NA group the phases presented: final ovulatory > initial ovulatory > menstrual > luteal. The AT group presented: initial ovulatory, final ovulatory and luteal > menstrual periods, with a higher subjective perception of effort in both groups for the menstrual and luteal periods. The results found in this study indicate that there is an influence of the menstrual cycle on the total training volume and on the subjective perception of effort. Greater performance was observed when performing a complete training for lower limbs during the ovulatory phase, as well as the perception of fatigue was greater in the menstrual and luteal phases.